Pengalaman Kekerasan pada Pedagang Kaki Lima di Indonesia - Salma Nur Rahama; Rina Hermawati (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
This study aims is to describe about the violence experience against street vendors in Indonesia including the causes of violence, forms of violence and street vendors' experience responses to the violence. This research uses qualitative methods with collecting data techniques from literature studies such as ,notes, books, papers or articles, journals and so on. The research results showed that the causes of street vendor violence are related to the class that have more power and the class that have less power. The power in question is the power or strength that a person has to do what he wants. The forms of violence experienced by street vendors can be identified into three forms based on Galtung's theory, including direct violence that can be seen such as physical, verbal and sexual violence, then the second is structural violence, namely violence that is not perpetrated by individuals but is hidden in a structure both smaller and smaller structures. broader structure, then the third is cultural violence, namely the symbolic space that exists in the cognition system and can be a driving force for both direct and structural violence. PKL responses to the violence they experience are divided into two, namely resisting and not resisting.